2017
DOI: 10.1038/bjc.2017.224
|View full text |Cite
|
Sign up to set email alerts
|

Novel immunohistochemistry-based signatures to predict metastatic site of triple-negative breast cancers

Abstract: Background:Although distant metastasis (DM) in breast cancer (BC) is the most lethal form of recurrence and the most common underlying cause of cancer related deaths, the outcome following the development of DM is related to the site of metastasis. Triple negative BC (TNBC) is an aggressive form of BC characterised by early recurrences and high mortality. Athough multiple variables can be used to predict the risk of metastasis, few markers can predict the specific site of metastasis. This study aimed at identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 76 publications
0
22
0
Order By: Relevance
“…Five studies reported a statistically significant multivariable association between young age and risk for BCBM with effect estimates ranging between 1.66 -2.7 [17,25,26,44,80], whilst no significant association was found in the rest of the studies considering solely HER2-positive patients, likely reflecting the small sample size used [20, 23-25, 61, 81]. Similarly, in the subset of studies involving TNBC patients, age was not found to impact BCBM [24,39,71].…”
Section: Agementioning
confidence: 96%
See 4 more Smart Citations
“…Five studies reported a statistically significant multivariable association between young age and risk for BCBM with effect estimates ranging between 1.66 -2.7 [17,25,26,44,80], whilst no significant association was found in the rest of the studies considering solely HER2-positive patients, likely reflecting the small sample size used [20, 23-25, 61, 81]. Similarly, in the subset of studies involving TNBC patients, age was not found to impact BCBM [24,39,71].…”
Section: Agementioning
confidence: 96%
“…In total, 69 studies were identified investigating predisposing factors for BCBM [10,12,. The majority of the included studies involved patients of all BC subtypes; thirteen reported risk factors for BM in HER2positive patients [17, 20, 23-27, 44, 47, 61, 66, 80, 81] and three in TNBC patients [24,39,71]. Twelve studies compared clinicopathological characteristics of BCBM patients that developed BM as a first site of relapse, with those who first developed metastases elsewhere [10,12,21,28,30,31,39,46,54,63,66,73].…”
Section: Group a -Prognostic Factors Associated With The Risk For Bcbmmentioning
confidence: 99%
See 3 more Smart Citations